Challenges and Progress with Diagnosing Pulmonary Tuberculosis in Low- and Middle-Income Countries - Anthony D. Harries; Ajay M.V. Kumar (Diagnostics, 2018)
Case finding and the diagnosis of tuberculosis (TB) are key activities to reach the World Health Organization’s End TB targets by 2030. This paper focuses on the diagnosis of pulmonary TB (PTB) in low- and middle-income countries. Sputum smear microscopy, despite its many limitations, remains the primary diagnostic tool in peripheral health facilities; however, this is being replaced by molecular diagnostic techniques, particularly Xpert MTB/RIF, which allows a bacteriologically confirmed diagnosis of TB along with information about whether or not the organism is resistant to rifampicin within two hours. Other useful diagnostic tools at peripheral facilities include chest radiography, urine lipoarabinomannan (TB-LAM) in HIV-infected patients with advanced immunodeficiency, and the loop-mediated isothermal amplification (TB-LAMP) test which may be superior to smear microscopy. National Reference Laboratories work at a higher level, largely performing culture and phenotypic drug susceptibility testing which is complemented by genotypic methods such as line probe assays for detecting resistance to isoniazid, rifampicin, and second-line drugs. Tuberculin skin testing, interferon gamma release assays, and commercial serological tests are not recommended for the diagnosis of active TB. Linking diagnosis to treatment and care is often poor, and this aspect of TB management needs far more attention than it currently receives.